Higher Abundance of Sediment Methanogens and Methanotrophs Do Not Predict the Atmospheric Methane and Carbon Dioxide Flows in Eutrophic Tropical Freshwater Reservoirs - Pierangeli, Gabrielle Maria Fonseca; Domingues, Mercia Regina; Jesus, Tatiane Araujo de; Coelho, Lúcia Helena Gomes; Hanisch, Werner Siegfried; Pompêo, Marcelo Luiz Martins; Saia, Flávia Talarico; Gregoracci, Gustavo Bueno; Benassi, Roseli Frederigi (Frontiers in Microbiology, 2021)
Freshwater reservoirs emit greenhouse gases (GHGs) such as methane (CH4) and carbon dioxide (CO2), contributing to global warming, mainly when impacted by sewage and other anthropogenic sources. These gases are produced by microbial organic carbon decomposition, but little is known about the microbiota and its participation in GHG production and consumption in these environments. In this paper we analyzed the sediment microbiota of three eutrophic tropical urban freshwater reservoirs, in different seasons and evaluated the correlations between microorganisms and the atmospheric CH4 and CO2 flows, also correlating them to limnological variables. Our results showed that deeper water columns promote high methanogen abundance, with predominance of acetoclastic Methanosaeta spp. and hydrogenotrophs Methanoregula spp. and Methanolinea spp. The aerobic methanotrophic community was affected by dissolved total carbon and was dominated by Crenothrix spp. However, both relative abundance of the total methanogenic and known methanotrophic communities in sediments were uncoupled to CH4 and CO2 flows. Network based approach showed that fermentative microbiota, including Leptolinea spp. and Longilinea spp., which produces substrates for methanogenesis, is shown to influence CH4 flows and was favored by anthropogenic pollution, such as untreated sewage loads. Additionally, less polluted conditions favored probable anaerobic methanotrophs such as Candidatus Bathyarchaeota, Sva0485, NC10 and MBG-D/DHVEG-1, which promoted lower gaseous flows, confirming the importance of sanitation improvement to reduce these flows in tropical urban freshwater reservoirs and their local and global warming impact.